SPOROZOAN INFECTION IN PENAEUS SEMISULCATUS AT MANDAPAM - Thomas, M M (Indian Journal of Fisheries, 2011)
A few specimens of Penaeus semisulcatus collected from Mandapam area were found infected with a microsporidian parasite tentatively identified as Thelohania duorara Iversen and Manning whicli has ’been earlier reported only from the. U.S.A. Although these parasites resemble T. duorara’ closely, they differ significantly from the American specimens in the shape of the spores, and pansporoblasts.